The effect of sustainability reporting on corporate value with earnings quality as mediating variable - Paulus Tangke; Suwandi Ng; Ardi Wongso (Manajemen dan Bisnis, 2022)
The purpose of this research was to examine the effect of sustainability reporting economic, environment, and social aspect on corporate value mediated by earnings persistence, and earnings timeliness. This research used purposive sampling method that was the selected samples that meet predetermined criteria, so the number of samples that meet the criteria was 16 companies for each period from the entire population of non-financial companies listed on the Indonesia Stock Exchange in 2016 – 2019. The data analytical method used in this research was path analysis and mediation hypothesis analysed by using sobel test. The result of analysis shows that sustainability reporting economic aspect has negative but not significant, environment aspect has negative and significant, and social aspect has positive and significant relationship on the earnings persistence. While sustainability reporting economic, environment, and social aspect have positive but not significant effect on the earnings timeliness. Then, sustainability reporting economic aspect has positive but not significant relationship on the corporate value, environment and social aspect have negative and significant effect on the corporate value. Accordingly with earnings persistence has negative but not significant effect on corporate value. While earnings timeliness has positive and significant effect on the corporate value. This research also shows that earnings persistence and earnings timeliness do not mediate the effect of sustainability reporting economic, environment, and social aspect on corporate value. Keywords: sustainability reporting, earnings quality, corporate value